Pemanfaatan Rempah Rumah Tangga untuk Meringankan Pegal Linu - Agnes Rendowaty; Ade Arinia Rasyad; Nilda Lely; Masayu Azizah; Ema Ratna Sari; Erjon Erjon; Dewi Patmayuni; Lilik Pranata; Masayu Rosyidah (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
Muscle pain is a common muscle pain experienced by people. Actually, there are household spices that can be used to reduce muscle pain, including ginger, turmeric, galangal, and pepper, etc., therefore the community service activity team aims to provide education about the benefits of Household Spices to Relieve Muscle Pain. The activity method is by means of education and introduction of Household Spices to Relieve Muscle Pain, the activity was carried out on Elementary and Middle School Teachers of the Ummul Quro Al-Hamidiyah Foundation Jl. Kyai Muara Ogan Kertapati Palembang Mosque, totaling 15 people on December 19, 2024. The results of the activity stated that the teachers understood the Utilization of Household Spices to Relieve Muscle Pain.